2023
DOI: 10.1080/07391102.2023.2180435
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy simulation of solvation effects on a G-quadruplex

Abstract: It is commonly believed that solvation of a polar molecule in a polar solvent has the only effect of red shifting all of his spectroscopical features, similarly solvating a polar molecule in a non polar solvent has the opposite effect. Naturally this can be retained valid for very simple molecular systems, but what are the effects of solvation to more complex molecular systems ?. A theoretical analysis of different kind of systems can be helpful to give atomistic insights to answer these questions, and also he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Notice that in case of a truly separable potential, we could write V 3 ( q̃ 3 ) – V 3 ( q̃ 3 eq ) = V ( q̃ 1 , q̃ 2 , q̃ 3 ) – V ( q̃ 1 , q̃ 2 , q̃ 3 eq ) and V 1,2 ( q̃ 1 , q̃ 2 ) – V 1,2 ( q̃ 1 eq , q̃ 2 eq ) = V ( q̃ 1 , q̃ 2 , q̃ 3 ) – V ( q̃ 1 eq , q̃ 2 eq , q̃ 3 ). These last expressions correspond to the “projected potentials” used to compute the vibrational spectroscopic features of molecules as large as G-quadruplex in solution with the Divide-and-Conquer SemiClassical Initial Value Representation (DC-SCIVR) method. ,, While the DC-SCIVR method simulates the dynamics of a system under a full dimensional potential and then approximates the classical action with a potential projected into subspaces, the algorithm we are presenting here evolves the dynamics entirely under the subspace-projected potential (or partially projected, when α ≠ 0). Furthermore, the decoupling could be applied to all the degrees of freedom pertaining to two atoms, that is, for instance, to the Cartesian product ( x 1 , y 1 , z 1 ) × ( x 2 , y 2 , z 2 ), to decouple atoms 1 and 2.…”
Section: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that in case of a truly separable potential, we could write V 3 ( q̃ 3 ) – V 3 ( q̃ 3 eq ) = V ( q̃ 1 , q̃ 2 , q̃ 3 ) – V ( q̃ 1 , q̃ 2 , q̃ 3 eq ) and V 1,2 ( q̃ 1 , q̃ 2 ) – V 1,2 ( q̃ 1 eq , q̃ 2 eq ) = V ( q̃ 1 , q̃ 2 , q̃ 3 ) – V ( q̃ 1 eq , q̃ 2 eq , q̃ 3 ). These last expressions correspond to the “projected potentials” used to compute the vibrational spectroscopic features of molecules as large as G-quadruplex in solution with the Divide-and-Conquer SemiClassical Initial Value Representation (DC-SCIVR) method. ,, While the DC-SCIVR method simulates the dynamics of a system under a full dimensional potential and then approximates the classical action with a potential projected into subspaces, the algorithm we are presenting here evolves the dynamics entirely under the subspace-projected potential (or partially projected, when α ≠ 0). Furthermore, the decoupling could be applied to all the degrees of freedom pertaining to two atoms, that is, for instance, to the Cartesian product ( x 1 , y 1 , z 1 ) × ( x 2 , y 2 , z 2 ), to decouple atoms 1 and 2.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…When the time-evolution algorithm described in the next sections is applied to such a system, the evolution of the system is artificially separable, and the potential is up to the second order of the type , q2 eq , q3). These last expressions correspond to the "projected potentials" used to compute the vibrational spectroscopic features of molecules as large as G-quadruplex in solution 40 with the Divide-and-Conquer SemiClassical Initial Value Representation (DC-SCIVR) method. 14,15,20 While the DC-SCIVR method simulates the dynamics of a system under a full dimensional potential and then approximates the classical action with a potential projected into subspaces, 14 the algorithm we are presenting here evolves the dynamics entirely under the subspace-projected potential (or partially projected, when α ≠ 0).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In several previous works, we have demonstrated that QCT calculations based on a single, energetically tailored trajectory are effective in the description of the classical spectroscopy of molecular species. An educated guess for the initial conditions consists of selecting an initial geometry ( q 0 ) corresponding to the equilibrium one ( q eq ) while adopting a harmonic estimate for the initial linear momenta ( p 0 ) true{ .25ex2ex q 0 false( j false) = q eq false( j false) p 0 false( j false) = q 0 false( j false) false| q 0 false( j false) false| ( 2 n j + 1 ) ω j where ω j is the harmonic frequency of the j -th degree of freedom and n j is its vibrational quantum number. By setting n j = 0 for all degrees of freedom, the system has an initial energy equal to the harmonic zero point energy (ZPE), which is a suitable value to explore an adequate portion of the PES.…”
Section: Theoretical Detailsmentioning
confidence: 99%
“…On the other hand, this flexibility allows for the formation of other tertiary structures, such as B-DNA, A-DNA, or even triple-stranded DNA . Different base clusters are also possible, such as the Hoogsteen pairs and G-quadruplexes. , Given the presence of keto and amino groups, nucleobases present a great number of tautomers, a characteristic that can induce mismatches during the replication processes . Even if ribonucleic acid (RNA) is the nucleic acid most affected by non-canonical pairing, the nucleobase pair with the highest number of stable tautomers is guanine–cytosine (GC), which is in common with DNA.…”
mentioning
confidence: 99%
“…DC SCIVR is an acknowledged method, capable of accounting for anharmonicity and reproducing quantum effects, such as zero-point energy (zpe), overtones, and combination bands, using a single classical trajectory. This allows us to limit the computational effort even when investigating the 29 atom guanine–cytosine pair. DC SCIVR has already been applied with success to the vibrational study of isolated and solvated nucleobases and to other nucleotide-based macromolecules. ,,, The goal of these DC SCIVR spectra is to assign the experimental features on a solid footing and clear the open issues about both the structure and stability of the nucleobase pairs.…”
mentioning
confidence: 99%